Pneumoperitoneum caused by tuberculosis - Martínez, Sonia; Arroyo Martín, Juan José; Patiño Bernal, Begoña; Valdivia Pérez, Antonio (Cirugía del Uruguay, 2021)
86-year-old male who came to the emergency room due to lower limb edema. On examination, he presented discreet abdominal discomfort, with no other accompanying symptoms. The analysis shows a hemoglobin of 8.2 g / dL with a hematocrit of 24%. A chest and abdominal CT scan was performed (Fig. 1) that revealed bilateral pulmonary nodules with an inflammatory appearance, pleural effusion and massive pneumoperitoneum, without evidence of rupture of the hollow viscus. He is kept on an absolute diet and antibiotic therapy and parenteral nutrition are started. Cultures are extracted, mycobacteria appearing in the bronchoalveolar lavage. He is diagnosed with disseminated tuberculosis. The antibiotic treatment is adjusted and the patient improves progressively, being discharged from hospital 10 days after the onset of the symptoms. In the follow-up CT scan at 3 months, the pneumoperitoneum has disappeared. The most frequent origin of spontaneous non-surgical pneumoperitoneum is the thorax (due to tuberculosis, mechanical ventilation, barotrauma, pulmonary contusion, chronic obstructive pulmonary disease…), there are also abdominal causes such as intestinal cystic pneumatosis. Between 5 and 14% of patients with spontaneous pneumoperitoneum can be managed conservatively, without surgery. Some series show that no visceral perforation is evident in up to 44% of non-surgical pneumoperitoneums. It is therefore a cause of non-surgical pneumoperitoneum that, with an adequate clinical and therapeutic approach, makes it possible to avoid surgical intervention. 1,2,3,4,5